Toponymy of Ancient Eastern Algeria and Its Role in Understanding Major Civilizational Changes in the Region - Daas, Fares (The Algerian Historical Journal, 2026)
This study aims to shed light on the toponymy of ancient eastern Algeria and how to benefit from it in understanding the political and cultural transformations in the region. This is done by tracing the toponymic presence of some models of the city and the countryside in ancient literary and material sources, such as Cirta, Sitifis, Thamugadi, and Medracen. The study concluded that the toponymic transformations in ancient eastern Algeria were closely linked to the major civilizational transformations that the region witnessed, as the names of cities and landmarks changed in accordance with political and cultural changes. The study confirmed that most of the names of cities in ancient eastern Algeria are of local origin.